Metrics at Work : Journalism and the Contested Meaning of Algorithms - Christin, Angele (Book collections on Project MUSE., 2020)
"Metrics at Work examines how digital metrics and analytics are transforming work practices, professional cultures, and organizational structures in today's economy. The author focuses on journalism, a field that is undergoing massive transformations because of digital technologies. The book follows two news websites with high editorial ambitions, the Paris-based LaPlace and New York City-based TheNotebook, revealing many similarities within each company-their editorial goals, technological tools, and even office furniture among them-as they face growing pressure to attract more traffic and increase their clicks. But beyond these similarities, Metrics at Work uncovers a striking difference between these French and American news sites: the ways in which journalists understand and respond to the analytics. The author draws on four years of ethnographic fieldwork, including over one hundred interviews with American and French journalists, to examine this divergence. While the American journalists routinely disregarded traffic numbers and rely more on the opinion of their peers to define journalistic quality, the French journalists fixated on internet traffic and viewed the numbers as a signal of involvement in the public sphere. Christin offers a cultural explanation, arguing that the historical differences between the two journalistic traditions continue to structure the very different ways that journalists today make sense of audience measurements"--